STUDI KASUS PEMBERIAN KOMBINASI KOMPRES HANGAT DAN MASSAGE KEPALA UNTUK MENGATASI MASALAH KEPERAWATAN NYERI AKUT PADA PASIEN HIPERTENSI - Indraswari, Desak Gede Francin; Yunita Sari, Ni Luh Putu Dian; Prihandhani, IGAA Sherlyna (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
Hypertensive patients who experience an increase in blood pressure have several complaints, one of which is headache. This impact causes a nursing problem, namely acute pain. Management is required to reduce these effects by providing head massage combined with warm compresses. This scientific study was conducted to determine the nursing care profile of hypertensive patients with acute pain as a nursing issue, who were given head massage combined with warm compresses in Pujungan Village, the working area of the Pupuan I Health Center. A descriptive method with a case study approach to the nursing care process was used in managing clients with acute pain, including assessment, nursing diagnosis, intervention, implementation, and evaluation. Patients were selected using purposive sampling in Pujungan Village, the working area of the Pupuan I Health Center. The final nursing research involved three patients who received head massage combined with warm compresses for 30 minutes. The evaluation of the intervention showed that all three patients, who initially reported moderate pain, experienced mild pain after receiving head massage combined with warm compresses, indicating that the acute pain nursing issue had been resolved. The administration of head massage combined with warm compresses can alleviate acute pain in hypertensive patients. Therefore, it is recommended that hypertensive patients be given head massage combined with warm compresses to alleviate acute pain.